2017
DOI: 10.1093/nar/gkw1366
|View full text |Cite
|
Sign up to set email alerts
|

FACT is a sensor of DNA torsional stress in eukaryotic cells

Abstract: Transitions of B-DNA to alternative DNA structures (ADS) can be triggered by negative torsional strain, which occurs during replication and transcription, and may lead to genomic instability. However, how ADS are recognized in cells is unclear. We found that the binding of candidate anticancer drug, curaxin, to cellular DNA results in uncoiling of nucleosomal DNA, accumulation of negative supercoiling and conversion of multiple regions of genomic DNA into left-handed Z-form. Histone chaperone FACT binds rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
178
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(193 citation statements)
references
References 89 publications
(155 reference statements)
10
178
0
5
Order By: Relevance
“…10 Despite many clinical trials, over the past 20 years, no real improvements have been made regarding outcome or prognosis for patients with MLL-r leukemia. 13,[20][21][22] Here, we confirm that CBL0137 induced p53 pathway activation and an IFN response in MLL-r leukemia models in vivo. In our study, we demonstrated that the curaxin CBL0137 has antileukemic effects in preclinical in vitro and in vivo models of MLL-r leukemia at doses that are well tolerated in mice.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…10 Despite many clinical trials, over the past 20 years, no real improvements have been made regarding outcome or prognosis for patients with MLL-r leukemia. 13,[20][21][22] Here, we confirm that CBL0137 induced p53 pathway activation and an IFN response in MLL-r leukemia models in vivo. In our study, we demonstrated that the curaxin CBL0137 has antileukemic effects in preclinical in vitro and in vivo models of MLL-r leukemia at doses that are well tolerated in mice.…”
Section: Discussionsupporting
confidence: 76%
“…[45][46][47] In addition, as CBL0137 can act through a number of anticancer mechanisms, including inhibition of the NFκB pathway, activation of the p53 pathway, c-trapping of FACT and induction of an IFN response, 13,[20][21][22] it is possible that the CBL0137-induced inhibition of cancer cell growth is mediated by different mechanisms in different cancer cells. It is possible that in vitro, the anticancer action of CBL0137 is predominantly mediated through its FACT-dependent action of NFκB pathway inhibition, and not through induction of an IFN response.…”
Section: Cancer Therapy and Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixing and imaging cells 30 min after rapamycin addition showed that nuclei positive for PCNA foci were also positive for H3.1‐EGFP foci, whereas nuclei negative for PCNA foci were also negative for H3.1‐EGFP foci (Fig B). Cells absent of PCNA foci, and by deduction not replicating their genomes, demonstrated a nucleolar enrichment of H3.1‐EGFP, which has previously been shown to be an artefact of excess soluble histones in the nucleus (Musinova et al , ; Safina et al , ).…”
Section: Resultsmentioning
confidence: 92%
“…CBL0137 binds to DNA but, unlike conventional DNA intercalating agents, it is non-mutagenic and hence was shown not to induce a DNA damage response (3). Instead, CBL0137 binding to DNA causes a prevalence of alternative DNA structures and destabilized nucleosomes which FACT recognizes and consequentially becomes trapped at (4). This leads to cell death via FACT-dependent activation of p53 as well as downregulation of a subset of NF-κB-dependent genes (3).…”
mentioning
confidence: 99%